Norm's benefit awareness in open normative multi-agent communities: A conceptual framework - Itaiwi A.-M.K.; Ahmad M.S.; Mahmoud M.A.; Tang A.Y.C. (Springer Verlag, 2023)
In open normative multi-agent communities, agents adopt new norms to increase their utilities. Several studies have developed mechanisms for agents to adopt new norms. These mechanisms are based on sanction, imitation, or social learning. The limitation of these mechanisms is that over time all agents follow the new norms, while in a real situation, usually there is a number of agents that persistently violate the norms for their benefits. We consider that intelligent agents should adopt new norms based on their awareness of the norms' expected benefits on their utilities and not only by sanctions or imitating other agents. Consequently, this paper presents a conceptual framework for agents' awareness of norms' benefits in open normative multi-agent communities. In the proposed framework, four components constitute agents' awareness of norms' benefits which are Norm's Adoption Ratio; Norm's Yields; Norm's Trust, and Norm's Morality. Using these components, however, agents would be able to evaluate the benefits of detected norms and subsequently determine whether the norms increase or decrease their utilities for eventual adoption or rejection. © Springer International Publishing Switzerland 2014.